(untitled) (Vietnam Journal of Community Medicine, 2026)
Physical activity (PA) plays a crucial role in maintaining and improving population health, contributing to the reduction of non-communicable diseases such as cardiovascular diseases, diabetes, and obesity. This study aimed to determine the prevalence of preventive medicine students at Hanoi Medical University who meet the World Health Organization (WHO) recommendations for physical activity, as well as to identify associated factors, using the Global Physical Activity Questionnaire (GPAQ). A cross-sectional study was conducted among 384 students from the first to the sixth year. Factors associated with meeting the recommended level of physical activity were identified using logistic regression analysis. The results showed that 59.9% of students met the WHO recommendations for physical activity. The proportion of students with high levels of physical activity according to WHO recommendations was 26%, with a higher proportion among males (37.1%) compared to females (19.7%). Students with excellent academic performance were more likely to meet the recommended physical activity levels than those with good academic performance (p < 0.05). Additionally, semester grade point average and monthly allowance were significantly associated with meeting the recommended level of physical activity.